Chemical composition and antifungal effect of hydroalcoholic extract of Allium tripedale (Tvautv.) against Candida species - Maryam Shirani; Azin Samimi; Heibatullah Kalantari; Mahboobeh madani; Ali Kord Zanganeh (Mazandaran University of Medical Sciences, 2017)
Background and Purpose: Treatment of life-threatening fungal infections caused by Candida species has become a major problem. Candida spp. are the most important causative agents of candidiasis. Allium tripedale is a medicinal plant that has been traditionally used to treat infections. In the present study, we aimed to determine the chemical compounds and antimicrobial activity of hydroalcoholic extract of A.tripedale against different species of Candida. Materials and Methods: Phytochemical analysis was performed to identify the possible bioactive components of this extract by using gas chromatography and mass spectroscopy (GC-MS). The hydroalcoholic extract of A. tripedale were collected.Different concentrations of A. tripedale (50, 25, 12.5, and 6.25 mg/ml) were used to evaluate its antifungal activity against Candida species (C. albicans, C. parapsilosis,and C. krusei) using disk diffusion assay. Results: The GC-MS analysis revealed the presence of 40 different phytoconstituents with peak area; the major compounds were tetracosane, hexadecanoic acid, 1-eicosanol, 1,2-dihydro-pyrido[3,2,1-kl]phenothiazin-3-one, 2-hexadecen-1-ol, and 3,7,11,15-tetramethyl. Hydroalcoholic extract showed strong antimicrobial activity (inhibition zone ⩾ 20 mm), moderate antimicrobial activity (inhibition zone < 12-20 mm), and no inhibition (zone < 12 mm). In addition, the hydroalcoholic extract exhibited the highest antimicrobial properties against C. albicans strains. Conclusion: A. tripedale extract had a considerable inhibitory effect against various Candida species, but its highest inhibitory effect was against Candid albicans. Further investigations are required to detect the performance of this plant in the treatment of Candida infection.